2018
DOI: 10.1002/hed.25056
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sal classification to parotid gland fine‐needle aspiration cytology: 10‐year retrospective analysis of 312 patients

Abstract: We believe that the Sal classification has a great potential to be a useful tool in classification of parotid gland cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In 2016, Bajwa et al [8] revised the Milan cytology classification and reported the Sal classification. Kilavuz et al [9] evaluated the Sal classification in 312 patients with salivary gland tumors and concluded that this classification was useful. Several validation studies have been conducted for the Milan system, as well, and its effectiveness was reported [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Bajwa et al [8] revised the Milan cytology classification and reported the Sal classification. Kilavuz et al [9] evaluated the Sal classification in 312 patients with salivary gland tumors and concluded that this classification was useful. Several validation studies have been conducted for the Milan system, as well, and its effectiveness was reported [10][11][12].…”
Section: Discussionmentioning
confidence: 99%